Comparison of Detergents, Their Additives, Crude Extracts of Biodetergents and Lipases Plus Mineral Solution in the Bioremediation of Soil Impacted by Hydrocarbons - Blanca Celeste Saucedo-Martinez; Liliana Marquez-Benavides; Juan Manuel Sánchez-Yáñez (Research Highlights in Science and Technology Vol. 6, 2023)
This chapter highlight (a) to analyze biostimulation of soil impacted by WMO with Eficaz®, Salvo® and Savia Gel® plus mineral solution; (b) to study in soil impacted by WMO biostimulation with polyethylene glycol, sodium tripolyphosphate plus mineral solution (c) to improve in soil impacted by WMO biostimulation with Tween 80, Triton X-100, with crude extracts of biodetergents and lipases, plus a mineral solution to reduce the WMO to a value below the maximum of 4,400 ppm of NOM-138 SEMANART/SSA1-2012 (NOM-138) to regard as bioremediated. In biostimulation of agricultural soil impacted by 60,000 ppm of waste motor oil (WMO), it is neither completely solubilized with a detergent nor removed as expected with a mineral solution. For this reason, in the biostimulation of soil impacted by WMO, pure detergents are applied: Tween-80 and Trition-X 100 or commercial detergents: Eficaz®, Salvo® and Savia Gel®, ignoring the effect of their additives: polyethylene glycol or sodium tripolyphosphate, in the emulsification of WMO emulsification. Nor if the application of combining crude extracts of biodetergents and lipases plus a mineral solution is more effective in the bioremediation of that soil. In this sense, the production of CO2 by WMO oxidation and its concentration by Soxhlet were measured. The experimental data were validated by Tukey HSD ANOVA. The results showed that the soil impacted with 60,000 ppm of WMO biostimulated with Salvo®, Eficaz® plus mineral solution, had maximum CO2 production on day 45 with 10.42 mg CO2/100 g and WMO decreased from 60,000 ppm to 21,700 ppm. In soil impacted by WMO biostimulated with sodium tripolyphosphate and mineral solution, in 40 days it reached 9.2 mg CO2/100 g of soil. In soil impacted by WMO biostimulated with Tween 80, Triton X-100, crude extracts of biodetergent and lipases plus mineral solution, the maximum CO2 production was reached and the highest of WMO decrease from 60,000 ppm to 1,600 ppm. In soil impacted by WMO biostimulated by crude extracts of biodetergents and lipases plus mineral solution, not biostimulated by Tween 80 or Triton X-100, WMO decreased from 60,000 to 2,000 ppm. This result shows in biostimulation of soil polluted by WMO applying crude extracts of biodetergents and lipases are better than the use of commercial with its additives and pure detergents plus mineral solution in the removal of WMO for soil bioremediation according to NOM-138.